To solve the inequality \( x - \frac{1}{3} \leq \frac{1}{2} \), we start by isolating \( x \).
- Add \( \frac{1}{3} \) to both sides of the inequality:
\[ x \leq \frac{1}{2} + \frac{1}{3} \]
- To add the fractions, we need a common denominator. The least common multiple of 2 and 3 is 6. Therefore, we convert the fractions:
\[ \frac{1}{2} = \frac{3}{6} \quad \text{and} \quad \frac{1}{3} = \frac{2}{6} \]
- Now we can add the fractions:
\[ \frac{1}{2} + \frac{1}{3} = \frac{3}{6} + \frac{2}{6} = \frac{5}{6} \]
Thus, we have:
\[ x \leq \frac{5}{6} \]
So the solution to the inequality \( x - \frac{1}{3} \leq \frac{1}{2} \) is:
\[ x \leq \frac{5}{6} \]
The correct response is \( x \leq \frac{5}{6} \).